DOA PUASA DI ANTARA KEPEMIMPINAN PENGGEMBALAAN, ROH KUDUS, DAN PERTUMBUHAN GEREJA - Sewie Elia Huang (Sekolah Tinggi Teologi Excelsius, 2020)
Abstract Fasting prayer has a very significant role for the growth of faith and congregation in the growth of the church because fasting prayer is their intimate relationship with God. The purpose of this paper answers the question: What is meant by fasting prayer? What is the relationship between fasting prayer and the Holy Spirit? What is the relationship between fasting prayer and shepherding leadership? What is the relation of fasting prayer in the growth of the Church? The research method uses descriptive literature research. The results of the study are: (1) fasting prayer is abstaining from all physical food for other bodies describing the consequences of fasting, namely: